CAN THE INTRODUCTION OF MARKETING PRINCIPLES PROMOTE THE DEVELOPMENT OF SPORTS ORGANIZATIONS IN MONTENEGRO? - Stevo Popović; Dragan Radovanović; Miomir Maroš; Molnar Slavko (Sport Scientific And Practical Aspects, 2025)
The subject matter of this research is marketing principles in the modern world with emphasis on sports organizations in Montenegro and the peculiarities of marketing in that field. The sample consisted of 101 respondents surveyed in different ways (by personal interview, mail or telephone) and selected by means of combination or hierarchical classification- in other words, the research included staff members occupying various important positions (presidents, secretaries, board of directors, coaches etc.) and working in different departments of these organizations ( Management, Marketing Department etc.). The study employed one of the most widely used research techniques- the survey, while the research tool used was a questionnaire consisting of 28 open-ended, closed-ended and Likert scale questions. Data analysis was based on frequency distribution, a commonly used data analysis procedure in descriptive statistics. It was established that the institution of marketing principles would further the development of sports organizations, and more significantly, ensure their sustainability and uninhibited functioning and that a proper combination of marketing principles would enhance communication with clients as well as contribute to a better management and restructuring of sports organizations.